Modelling and control of an adaptive tuned mass damper based on shape memory alloys and eddy currents. (4th August 2015) - Berardengo, M.; Cigada, A.; Guanziroli, F.; Manzoni, S.
Abstract: Tuned mass dampers have long since been used to attenuate vibrations. The need to make them adaptive in order to function even after changes of the dynamic characteristics of the system to be controlled has led to using many different technologies with the aim of improving adaptation performances. Shape memory alloys have already been proven to have properties suitable for creating adaptive tuned mass dampers for light structures. However, the literature has evidenced a number of issues concerning tuned mass dampers based on shape memory alloys, for instance the limited range of adaptation for the eigenfrequency of the damper. The present paper proposes a new layout for adaptive tuned mass dampers based on shape memory alloys, which allows to overcome many of the limitations and to reach a wide range of adaptation for the eigenfrequency. This layout relies on the use of shape memory alloy wires, so that the change of eigenfrequency is achieved by changing the axial load acting on these wires. The new tuned mass damper is then made fully adaptive by including a device that uses the principle of eddy currents, which allows also to change the damping of the tuned mass damper. Indeed, this new kind of damper is designed to dampen vibrations in systems excited by a random disturbance. The paper illustrates the layout and the model of the whole damper and validates it. This model moreover evidences all the advantages allowed by the new layout proposed. Finally, two different strategies to control the dynamic characteristics of the new adaptive tuned mass damper are presented and compared, both numerically as well as experimentally, so to illustrate strengths and drawbacks of each. The experiments and the simulations show that this new damper is fully capable of functioning when random excitation acts as disturbance on the system to control. Highlights: New adaptive tuned mass damper based on shape memory alloys and eddy current damper. Broad adaptation range for the device eigenfrequency. Low currents used and possibility to employ any kind of shape memory alloy.